Applications of Digital Image Processing in Microscope Images - ศิริสถิตกุล, เยาวเรศ (KKU Science Journal, 2012)
This article reviews the applications of digital image processing program in compositional, structural, and morphological characterizations of microscope images. Microscopes can be classified into optical microscopes, electron microscopes and scanning probe microscopes. The essential technique in the object analysis is the image segmentation which can be performed by the thresholding and the edge detection. The progress in research on different types of microscope images indicates that the characterization of composition, structure, and morphology can be effectively carried out.